Small‐Molecule‐based Supramolecular Plastics Mediated by Liquid‐Liquid Phase Separation. Issue 39 (24th August 2022) - Yu, Jingjing; Qi, Dawei; Mäkilä, Ermei; Lassila, Lippo; Papageorgiou, Anastassios C.; Peurla, Markus; Rosenholm, Jessica M.; Zhao, Zhao; Vallittu, Pekka; Jalkanen, Sirpa; Jia, Chunman; Li, Jianwei
Abstract: Plastics are one of the most widely used polymeric materials. However, they are often undegradable and non‐recyclable due to the very stable covalent bonds of macromolecules, causing environmental pollution and health problems. Here, we report that liquid‐liquid phase separation (LLPS) could drive the formation of robust, stable, and sustainable plastics using small molecules. The LLPS process could sequester and concentrate solutes, strengthen the non‐covalent association between molecules and produce a bulk material whose property was highly related to the encapsulated water amounts. It was a robust plastic with a remarkable Young's modulus of 139.5 MPa when the water content was low while became adhesive and could instantly self‐heal with more absorbed water. Finally, responsiveness enabled the material to be highly recyclable. This work allowed us to understand the LLPS at the molecular level and demonstrated that LLPS is a promising approach to exploring eco‐friendly supramolecular plastics that are potential substitutes for conventional polymers. Abstract : A liquid‐liquid phase separation (LLPS) was driven by the non‐covalent association of a disulfide bond linked azobenzene macrocycle with negative charges and a small cationic surfactant. The LLPS resulted in three‐dimensional supramolecular plastic materials that were highly adhesive at high water content and tough and stretchable at low water content. The resulting materials were also reusable and highly recyclable.